EPPDC: An Efficient Privacy-Preserving Scheme for Data Collection in Smart Grid - Jie Chen; Junping Shi; Yueyu Zhang (International Journal of Distributed Sensor Networks)
Different from the traditional grid, smart grid builds a real-time connection network between the user and the grid company by smart terminals, which can achieve bidirectional data transmission and information control. In smart grid, the smart meters send various information to the power generators and substations. Frequent data collection meets real-time management, but it tends to raise privacy concerns from the users about privacy information leakage. Based on the blind signature and the key distribution scheme, an efficient and privacy-preserving data collection (EPPDC) scheme is proposed for smart grid to cope with the above problems. In EPPDC scheme, the users' data information is transmitted to the local aggregator by building gateway with privacy preserving. In addition, the security analysis indicates that EPPDC scheme not only can resist replay attack, but also has source authentication and data integrity, confidentiality, unforgeability, nonrepudiation, and evolution of shared keys. Furthermore, performance analysis shows that EPPDC scheme has less computation cost than existing scheme.